1998
DOI: 10.2165/00044011-199816060-00002
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Differences in Pain Relief and Functional Improvement in Osteoarthritis with Diclofenac or Tramadol

Abstract: OA patients' response to analgesic treatment was highly individual and the response to one drug was not predictive of that to another drug. A significant proportion of patients were not treated satisfactorily with diclofenac or tramadol alone. The results obtained from a descriptive analysis of group effects (means, medians) were inappropriate for drawing conclusions on individual treatment benefits. Improvement of functional capability apparently was a consequence of pain relief. Effective pain relief should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 16 publications
0
16
0
6
Order By: Relevance
“…This is primarily explained by the findings of 1 study 17 that accounted for 74% of our meta-analysis, in which the authors compared dextropropoxyphene (a weak opioid) with diclofenac. In the other 2 comparisons of tramadol versus diclofenac 18 and controlled-release morphine versus nortriptyline 19 , the differences were not statistically significant.…”
Section: Effectiveness Of Opioids Compared With Other Drugsmentioning
confidence: 82%
“…This is primarily explained by the findings of 1 study 17 that accounted for 74% of our meta-analysis, in which the authors compared dextropropoxyphene (a weak opioid) with diclofenac. In the other 2 comparisons of tramadol versus diclofenac 18 and controlled-release morphine versus nortriptyline 19 , the differences were not statistically significant.…”
Section: Effectiveness Of Opioids Compared With Other Drugsmentioning
confidence: 82%
“…Correspondingly, patients experienced greater functional improvement in the overall WOMAC pain, stiffness and function scores in the present study, compared with the study, (26.8% versus 19.2% with tramadol, and 27.5% versus 24.8% with diclofenac). 17 But as evident from the graphs mean scores for all the parameters has substantially increased in all the treatment groups with maximum increase in DIC+PPI group reflecting its maximum efficacy compared to tramadol group. This can be because diclofenac gets distributed in synovial fluid and has chondro protective and other action as mentioned like blockage of voltage-dependent sodium channels and acid-sensing ion channels (ASICs), positive allosteric modulation of KCNQ-and BK-potassium channels.…”
Section: Efficacy Comparison Of Study Intergroups In Present Studymentioning
confidence: 83%
“…16 In an earlier study, IR tramadol was compared with IR diclofenac in OA patients. 17 Both medications were given as needed, to a maximum dose of 300mg/day for tramadol and 150mg/day for diclofenac. Correspondingly, patients experienced greater functional improvement in the overall WOMAC pain, stiffness and function scores in the present study, compared with the study, (26.8% versus 19.2% with tramadol, and 27.5% versus 24.8% with diclofenac).…”
Section: Efficacy Comparison Of Study Intergroups In Present Studymentioning
confidence: 99%
“…However, almost all of the available current OA therapies have temporary effects. Tramadol was reported to provide pain control when used as alternative or supplementary to NSAIDs in a study where it was compared to diclofenac (20). The American Geriatric Society reported that patients receiving chronic opioid therapy have fewer life-threatening risks than those who receive long-term NSAID therapy (21).…”
Section: Discussionmentioning
confidence: 99%